The Communicative Competence Components Analysis in Using English through EIR - Faradilla, Ayu Silvana; Rukmini, Dwi (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
This study was aimed to explain the communicative competence components of the fourth semester English Department students through English Interaction Room (EIR). The communicative competence components in using English were analyzed based on the grammatical competence, discourse competence, sociolinguistic competence and strategic competence. This study used qualitative method which means that the data of this study were explained by using descriptive analysis method. The result showed that (1) Mostly, the utterances of the participants were ungrammatical in syntax, while some were in morpheme, but those were acceptable (2) Mostly the utterances were appropriate with the topic discussed. the participants were able to construct a unified discourse, (3) Mostly, the utterances seemed natural and used less formal language, and (4) Most participants used achievement strategy to hold the conversation. In conclusion, most of EIR participants are communicative in using English viewed from the discourse competence, sociolinguistic competence and strategic competence. They need to increase their competence of using English grammar. Keywords: Communicative Competence; Using English; English Interaction Room (EIR).